Cybercrime's Impact on Personal Data Security - Mohammed Tayeb BELGHIT & Mounir ELHAMZA (Akofena)
Abstract: The growing impact of cybercrime on personal data security is becoming a major issue in the digital age. The concept of "black numbers" for unreported or undetected crimes complicates the assessment of the true extent of online offences. The sophistication of digital attacks, whether it’s data theft, scams or privacy breaches, reveals the vulnerability of existing security systems. The consequences of these violations are serious, affecting not only individuals' privacy and financial security but also confidence in digital infrastructures. In response to these challenges, the study highlights the need for collective vigilance and continuous improvement of safety practices. Data protection cannot be based on technological solutions alone; it also requires training and awareness of users. At the same time, security systems must be continually adapted to counter new forms of attack. Finally, collaboration between governments, private companies and citizens is essential to creating a safer digital environment. Governments must strengthen legislative frameworks and facilitate information sharing, while businesses must invest in more robust technologies. Only by uniting the efforts of all actors in cyberspace will it be possible to better prevent and manage emerging threats.